PERIAPICAL SURGERY: THE ISSUE OF RETROGRADE OBTURATION - Kacarska, Marina (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
The primary objective of periapical surgery is to eradicate the etiological agents of periapical lesions, to obtain hermetic apical seal, so the parodontium is restored to a state of biologic and functional health. Uncertain clinical and radiographic evaluation of canal obturation, coronary permeability that canâ€™t be detected during clinical investigation, are main arguments in favor of routine retro preparation and obturation. Reported clinical study aimed to evaluate particular preoperative and intraoperative tooth related aspects as potential predictors of retrograde obturation. Patients who were referred for periapical surgery of 45 teeth with chronic periapical inflammation associated with endodontic treatment were included in this study. Preoperative radiographs were evaluated for quality and extent of the canal obturation, as well as root and canal morphology. During periapical surgery, using visual enhancement, the following intraoperative aspects were evaluated: resected root surfaces, root contour, canal morphology, presence of iatrogenic mistakes, canal obturation in relation to retrograde obturation. The preoperative results showed prevalence of inadequate canal obturation (91,1%) in teeth with one root and one canal structure (93,3%). The intraoperative evaluation demonstrated prevalence of oval root surfaces (74,0%) with unobturated one canal structure (70,8%). Where obturation was present, leaking was detected (28,6%). Such findings undoubtedly pointed in favor of retro preparation. Preoperative evaluation of canal obturation in conjunction with intraoperative examination under visual enchantment of resected root surface confirmed the need for retrograde obturation. Therefore periapical surgery of teeth with periapical inflammatory lesions associated with canal treatment should include retrograde obturation thus primary goals are accomplished. Keywords:   periapical surgery, chronic periapical inflammation, retrograde obturation, canal obturation, radiography, root and canal morphology, resected root surface. https://doi.org/10.55302/JMS2251132k